Transient left ventricular function deterioration after patent ductus arteriosus closure: A case series - Mohammad Reza Sabri; Chehreh Mahdavi; Hamid Bigdelian; Ali Reza Ahmadi; Mehdi Ghaderian; Bahar Dehghan; Davood Ramezani Nezhad (SAGE Open Medical Case Reports)
There is growing evidence of left ventricular decompensation following the closure of the patent ductus arteriosus, which most often happens early in the post-surgical time and improves on its own a few months after. Here, we aim to present nine cases whose left ventricular ejection fraction deteriorated early or late after the procedure. There were nine patients diagnosed with patent ductus arteriosus by echocardiography. The patients presented with a murmur, easy fatigability, exercise intolerance, and poor weight gain. The age varied from 5 months to 41 years old. Patients developed left ventricular ejection fraction deterioration, starting from the day after the operation to 3 years after the closure. Pre-closure left ventricular ejection fraction ranged from 60% to 75% and post-closure from 33% to 59%. The range for shortening fraction (SF) was from 30% to 42% and 16% to 31%, respectively. The patent ductus arteriosus was moderate to large in all patients. One patient was finally diagnosed with dilated cardiomyopathy. Patients with patent ductus arteriosus show left ventricular ejection fraction deterioration up to years after closure, whether percutaneous or operative. Large patent ductus arteriosus is associated with more complications and reduced post-surgery cardiac function due to the amount of the shunt before closure.